2017
DOI: 10.1002/ece3.2963
|View full text |Cite
|
Sign up to set email alerts
|

Does selection on horn length of males and females differ in protected and hunted populations of a weakly dimorphic ungulate?

Abstract: Weaponry in ungulates may be costly to grow and maintain, and different selective pressures in males and females may lead to sex‐biased natural survival. Sexual differences in the relationship between weapon growth and survival may increase under anthropogenic selection through culling, for example because of trophy hunting. Selection on weaponry growth under different scenarios has been largely investigated in males of highly dimorphic ungulates, for which survival costs (either natural or hunting related) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…A similar analysis for female chamois, however, found no evidence of selection against individuals with rapidly-growing horns (Rughetti & Festa-Bianchet 2011). In another study of chamois, Corlatti et al (2017) found that early horn growth had strong effects on age at harvest for both sexes where hunters faced few restrictions or age preferences. Effects were weak for males in an area in Austria where hunters mostly harvested old males, and nonexistent for females in an area in Italy with restrictions on harvesting lactating females.…”
Section: What Do We Know About Hunter Selectivity?mentioning
confidence: 80%
See 1 more Smart Citation
“…A similar analysis for female chamois, however, found no evidence of selection against individuals with rapidly-growing horns (Rughetti & Festa-Bianchet 2011). In another study of chamois, Corlatti et al (2017) found that early horn growth had strong effects on age at harvest for both sexes where hunters faced few restrictions or age preferences. Effects were weak for males in an area in Austria where hunters mostly harvested old males, and nonexistent for females in an area in Italy with restrictions on harvesting lactating females.…”
Section: What Do We Know About Hunter Selectivity?mentioning
confidence: 80%
“…Red deer management in Hungary, and in central Europe in general, does not strongly select against largeantlered males and includes culling of males with small antlers, which could compensate for a possible evolutionary effect of trophy hunting (Mysterud & Bischof 2010). Decreases in both horn length and mass have been reported for hunted populations of chamois (Rughetti & Festa-Bianchet 2012, Mason et al 2014, Corlatti et al 2017) but those decreases appear more likely due to climate change than to selective hunting. Horn size appears to play a limited role in chamois male mating success (Corlatti et al 2015).…”
Section: Do Other Studies Of Hunted Ungulates Suggest An Evolutionarymentioning
confidence: 99%
“…In chamois, if trophy hunting partly reflects natural mortality, this species would be less susceptible to evolutionary consequences of selective harvesting. Temporal declines in both horn length and body mass reported in several populations of chamois (Corlatti et al, ; Mason, Willis, Chirichella, Apollonio, & Stephens, ; Rughetti & Festa‐Bianchet, ) appear to be caused by climate change, rather than selective hunting.…”
Section: Discussionmentioning
confidence: 95%
“…Density is particularly high in our population of chamois that has been at or close to carrying capacity since the 1980s. A recent study found no significant effect of early horn growth (L1–L2) on longevity in a protected population of Alpine chamois (Corlatti et al, ), possibly because population density relative to resource levels was not high enough. Our results also show that longevity does not necessarily capture the mortality pattern during early adulthood.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation